A simplified model for acoustic focalization in environments with seabed uncertainties - Qu, Ke; Ou, Zhenyi; Huang, Xin; Liu, Liwen (Frontiers in Physics, 2023)
Introduction: Parameter mismatch poses a challenge to source localization in cases involving environments with seabed uncertainties. By including environmental parameters in the search space, focalization can be used to estimate the location of the source using environmental information that is limited a priori. Methods: To reduce the number of parameters, a simplified seabed model is proposed here for such focalization. Only two geoacoustic parameters—the amplitude F and phase cF of reflection—are used to describe the seabed. Focalization is generally tested using genetic algorithms for the colored noise case (COLNOISE) benchmark problem. Results: The proposed simplified model can obtain the location of the source more easily than a layered model. Due to its advantage in terms of parameter sensitivity and inter-coupling, the simplified model can ensure the robustness of the results of inversion. The proposed method was tested on a broadband signal in the Asian Seas International Acoustics Experiment (ASIAEX2001), where both the location and the geoacoustic parameters were easily inverted. Discussion: The simplified model provides a sufficiently high acoustic resolution for focalization, and its reduction of the geoacoustic parameters helpes solve the problem of inversion.